Virtualized Traffic at Metropolitan Scales - Wilkie, David; Sewall, Jason; Li, Weizi; Lin, Ming C. (Frontiers in Robotics and AI, 2015)
Few phenomena are more ubiquitous than traffic, and few are more significant economically, socially, or environmentally. Any virtual reality system, including virtual globes and immersive multi-player worlds that are set in a modern or futuristic setting feature traffic systems. Virtual reality models can also aid in addressing the challenges of real-world traffic systems, the ever-present gridlock and congestion in cities worldwide: traffic engineers and planners can diagnose system instabilities and explore control strategies in virtual worlds reconstructed from available sensor data. To create these systems, road network models need to be created and represented. Traffic needs to be realistically and efficiently simulated. To analyze real-world scenarios, the traffic conditions need to be estimated and reconstructed. To create virtual scenarios, such as simulated cities, traffic needs to be intelligently and efficiently routed.